TAP-block as a component of multimodal analgesia for postoperative anesthesia in obstetrics and gynecology - Grigimalsky, Ye. V.; Garga, A. Y. (Pain medicine, 2018)
Postoperative pain relief is still quite actual problem in medicine, particularly in obstetrics and gynaecology. The most appropriate method of adequate post-operative anesthesia is multimodal analgesia. This article describes the features of multimodal analgesia using TAP-block combined with NSAIDs in obstetric and gynaecological patients, advantages and disadvantages of this combination and our own experience of applying this method in our clinic.